Bile affects production of virulence factors and motility of Vibrio cholerae. - Gupta, S (1997)
The effect of bile on the expression of cholera toxin (CT) and the major subunit of the toxin-coregulated pilus (TcpA) and on motility was examined in the Vibrio cholerae O1 classical-biotype strains 0395 and 569B. Although the motility of the cells increased significantly in the presence of bile, transcription of the ctxAB genes, encoding CT, and of the tcpA gene was drastically reduced. In toxR mutant strains, motility is higher than in the wild-type strain and was further increased, by about 150%, in the presence of bile. Bile represses CT production in strain 569B-55, a toxR mutant of strain 569B, which normally produces more than 80% of the amount of CT synthesized in the wild-type cells. These results suggest that bile may target some factor other than ToxR that is involved in the regulation of CT production and motility. Bile has no effect on the relative amounts of the two outer membrane porins, OmpU and OmpT, which are under ToxR control.